Influence of active subsystems on electric vehicle behavior and energy characteristics - Shyrokau, Barys (2015)
Nowadays there is a tendency to implement various active vehicle subsystems in a modern vehicle to improve its stability of motion, handling, comfort and other operation characteristics. Since each vehicle subsystem has own limits to generate supporting demand, their potential impact on vehicle dynamics should be analyzed for steady-state and transient vehicle behavior. Moreover, the additional research issue is the assessment of total energy consumption and energy losses, because a stand-alone operation of each vehicle subsystem will provide different impact on vehicle dynamics and they have own energy demands. The vehicle configuration includes (i) friction brake system, (ii) individual-wheel drive electric motors, (iii) wheel steer actuators, (iv) camber angle actuators, (v) dynamic tire pressure system and (vi) actuators generating additional normal forces through external spring, damping and stabilizer forces. A passenger car is investigated using commercial software. The actuator models are defined using experimental test results and technical literature information. The selected open-loop maneuvers cover steady-state and transient vehicle behavior. Slowly Steer Increasing maneuver demonstrated that all considered subsystems have notable influence on the steering characteristic of the vehicle in the transient area. For normal operation conditions, Step Steer maneuver in time-based domain and Sine Sweep maneuver in frequency domain are also investigated. For steady-state area, the cases of equivalent impact of each vehicle subsystem on the vehicle dynamics are defined. In such conditions the influence of stand-alone operation of vehicle subsystem on total energy consumption and energy losses was demonstrated for different steering frequencies.